Redefinisi Keputusan Konsumen dalam Jasa Transportasi Online: Menilai Faktor Kemudahan, Kepercayaan, dan Harga di Ekosistem Grab - Djatola, Hariyanto R; Hilal, Nur (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research Objectives: This research was conducted to see how far trust, price, and ease of service features offered by marketers can influence purchasing decisions to use Grab services among STIE Panca Bhakti Palu students. High competition in online transportation, requires you to survive with many online transportation services that continue to increase by improving the services and promotions provided to consumers and creating trust. Design/Method/Approach: The design of this research is explanatory research using qualitative and quantitative data using non-probability sampling in the form of accidental sampling with 80 respondents. The analysis tool uses multiple linear regressions and a quantitative research approach. Research Findings: The results of the study show that there is a significant and positive influence between trust, price, and ease of service features on purchasing decisions simultaneously, but on the other hand, partially testing only the ability of service features to influence the decision of users of grab transportation services, while trust and price have no effect. Theoretical Contributions and Originality: Trust and Security Theory; This theory highlights the importance of trust and security in influencing consumer behavior. Practical Implications: According to the results obtained from the responses of service users such as students, prices can be cheap or vice versa, but the convenience of the services provided is the biggest effect on consumer trust. Limitations of Research: This research has a limited scope in that the sample is only among students and not broadly representative of the wider community.